Membangun perpustakaan ramah disabilitas: menuju inklusi dan kesetaraan akses - zami, putri adz'biya zam (Maliki Interdisciplinary Journal, 2025)
This article discusses the importance of establishing disability-friendly libraries as a means of achieving inclusion and equitable access to information for people with disabilities. While access to information is a fundamental right, individuals with disabilities still face numerous barriers, both physical and non-physical. This article explores the criteria and standards for disability-friendly libraries, encompassing physical accessibility, technology, and services. Furthermore, it identifies implementation challenges, such as financial constraints, lack of awareness, limited human resources, and inadequate regulations. To overcome these obstacles, the article proposes a comprehensive strategy that includes integrated planning, strategic partnerships, effective socialization, ongoing monitoring and evaluation mechanisms, and the development of staff training curricula. By implementing this strategy, libraries can become inclusive and empowering learning centers for all members of society.